DISTRIBUTION PATTERN OF SAGO MARKETING (Metroxylon sp) IN THE MEKAR SARI VILAGE, OF MERBAU SUBDISTRICT MERANTI ISLAND DISTRICT - Fifi Rahmadani; Rudianda Sulaeman; Viny Volcherina Darlis (JURNAL ILMU-ILMU KEHUTANAN, 2018)
The marketing distribution is an economic action that affects the high and low income of farmers. Mekar Sari Village is a place to produce sago processed into sago flour. In the distribution pattern of farmers sago marketing as producers sell their farming products to toke / factory owners distribute their products to cooperatives and end up to consumers. In the distribution pattern there is an activity of activity, namely physical distribution. Transportation and marketing smoothnes are also problems because accessibility is so far that it affects the quality of sago flour. The purpose of this study was to determine the implementation of the distribution pattern of sago marketing and find out the physical distribution activities in each distribution pattern of marketing of sago in Mekar Sari Village, Merbau District, Meranti islands Regency. The method used was purposive sampling, a method considering samples taken from the criteria of respondents, sago farmers who settled in Mekar Sari Village, had sago plantation land in Mekar Sari Village, and could provide information to researchers. Data were analyzed using qualitative descriptive analysis method. Based on the results of the study that the distribution pattern of sago marketing in Mekar Sari Village, Merbau Subdistrict, Meranti Islands Regency, there are two forms of sago distribution marketing pattern, namely medium distribution patterns and long distribution patterns and physical distribution activities in each sago marketing distribution pattern in Mekar Sari Village, includes post-harvest handling of sago flour and transportation of sago flour using sea transportation access, namely barges.